Evocalcet prevents ectopic calcification and parathyroid hyperplasia in rats with secondary hyperparathyroidism - Sakai, Mariko; Tokunaga, Shin; Kawai, Mika; Murai, Miki; Kobayashi, Misaki; Kitayama, Tetsuya; Saeki, Satoshi; Kawata, Takehisa (PLOS ONE, 2020)
Background Elevated parathyroid hormone (PTH) levels in secondary hyperparathyroidism (SHPT) lead to vascular calcification, which is associated with cardiovascular events and mortality. Increased PTH production is caused by the excessive proliferation of parathyroid gland cells, which is accelerated by abnormal mineral homeostasis. Evocalcet, an oral calcimimetic agent, inhibits the secretion of PTH from parathyroid gland cells and has been used for the management of SHPT in dialysis patients. We observed the effects of evocalcet on ectopic calcification and parathyroid hyperplasia using chronic kidney disease (CKD) rats with SHPT. Methods CKD rats with SHPT induced by adenine received evocalcet orally for 5 weeks. The calcium and inorganic phosphorus content in the aorta, heart and kidney was measured. Ectopic calcified tissues were also assessed histologically. To observe the effects on the proliferation of parathyroid gland cells, parathyroid glands were histologically assessed in CKD rats with SHPT induced by 5/6 nephrectomy (Nx) after receiving evocalcet orally for 4 weeks. Results Evocalcet prevented the increase in calcium and inorganic phosphorus content in the ectopic tissues and suppressed calcification of the aorta, heart and kidney in CKD rats with SHPT by reducing the serum PTH and calcium levels. Evocalcet suppressed the parathyroid gland cell proliferation and reduced the sizes of parathyroid cells in CKD rats with SHPT. Conclusions These findings suggest that evocalcet would prevent ectopic calcification and suppress parathyroid hyperplasia in patients with SHPT.